2018
DOI: 10.4236/ojf.2018.81004
|View full text |Cite
|
Sign up to set email alerts
|

Stand Structure, Allometric Equations, Biomass and Carbon Sequestration Capacity of <i>Acacia mangium</i> Wild. (Mimosaceae) in Côte d’Ivoire

Abstract: In addition to bioenergy production, Acacia magium, a fast growing species, plays a major role in climate change mitigation through carbon sequestration from the atmosphere. The objective of this study was to improve estimates of aboveground biomass of 3, 7 and 11 years old stands of Acacia mangium set up through natural regeneration at Anguédédou in Côte d'Ivoire. Tree measurements were done in circular plots of 615 m 2 located at the center of each stand. 24 trees of circumference at breast height (cbh) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Equations to predict the TAGB were based on tree dbh and crown diameter. Such variations of allometric equations are in line with previous findings in Burkina Faso (Sawadogo et al 2010;Bayen et al 2015;Dimobe et al 2018a), Ghana (Henry et al 2010) and Côte d'Ivoire (Traoré et al 2018). The use of different sets of predictors also corroborates previous published equations where stem dbh was used as the lone predictor of woody species aboveground biomass or in combination with tree height and/or crown diameter (Kuyah et al 2012;Mbow et al 2013; Mensah et al The observed variations confirm the assumption that biomass predictors are specific to tree components (Dimobe et al 2018a).…”
Section: Aboveground Biomass and Dendrometric Relationshipssupporting
confidence: 89%
See 2 more Smart Citations
“…Equations to predict the TAGB were based on tree dbh and crown diameter. Such variations of allometric equations are in line with previous findings in Burkina Faso (Sawadogo et al 2010;Bayen et al 2015;Dimobe et al 2018a), Ghana (Henry et al 2010) and Côte d'Ivoire (Traoré et al 2018). The use of different sets of predictors also corroborates previous published equations where stem dbh was used as the lone predictor of woody species aboveground biomass or in combination with tree height and/or crown diameter (Kuyah et al 2012;Mbow et al 2013; Mensah et al The observed variations confirm the assumption that biomass predictors are specific to tree components (Dimobe et al 2018a).…”
Section: Aboveground Biomass and Dendrometric Relationshipssupporting
confidence: 89%
“…& Diels (Dimobe et al 2018b). However, tree stem was reported elsewhere as the greatest biomass fraction (Henry et al 2010;Sawadogo et al 2010;Fonseca et al 2011;Traoré et al 2018). The variations in biomass allocation patterns within and between species could be explained by the specific eco-physiological responses of woody plants to environmental factors.…”
Section: Distribution Of Aboveground Biomass and Carbonmentioning
confidence: 97%
See 1 more Smart Citation
“…Contrary, these results differed from those of Bagnoud and Kouyate [47] who have worked on savannah vegetation of Mali. As the total biomass, the best model of branch, and trunk biomasses was the allometric equation which was not influenced by the height as also found by Traore et al [48].…”
Section: Discussionsupporting
confidence: 71%
“…This result was similar to that of Bagnoud and Kouyate [49] who have worked on D. oliveri in Mali. As the total biomass, the best model of branches, trunks and root biomass was the equation 3 model which was not influenced by the height as found by Traore et al [50]. On the other hand, the best equation for the estimation of leaf biomass was obtained with the model of equation 4, integrating the tree diameter squared multiplied by the height (D 2 H), with RSE = 0.364; AIC = 17.836 and R 2 adj = 0.836.…”
Section: Discussionsupporting
confidence: 51%